A comparison of two circuit strength training programs on strength development of university aged males and females - Strelka, Robert A. (My University, 1985)
Twenty-four male and 29 female Ss were tested for strength development throughout a 2 day per week, 12 week circuit strength training program using Universal Gym equipment. Subjects were randomly divided into 2 training programs: (1) Group A -- 2 circuits of 10 reps using 75% of 1RM, and (2) Group B -- 2 circuits of 15 reps. using 50% of IRM. Thirty seconds of work followed by 30 sec's. of rest per machine was executed. One rep. max. strength tests were performed during weeks 1, 5, 8, and 12 on the leg press and bench press. A three-way ANOVA with repeated measures was used to calculate significant differences in strength development, while a Scheffe' post hoc comparison was used to determine significant pairs of mean scores. Analysis revealed that both training programs produced significant gains in strength. Males using either training program experienced greater gains in strength than females. Irregardless of sex, neither program was significantly superior to the other in overall strength gains. Male Ss in Group A experienced a greater rate of upper body strength gain among tests than males in Group B. Group A, irregardless of sex, produced a greater rate of upper body strength development among tests than Group B.
Keywords: Physiological aspects.; Circuit training.